A Calling, Not a Call of Duty: Public Librarians' Engagement with Immigrant Communities. Issue 2 (17th February 2022) - Dali, Keren
Abstract: Library and Information Science (LIS) literature on employee engagement is scarce, with most publications focusing on a related concept of job satisfaction. This article, however, contributes to an understanding of engagement experiences as manifested by public librarians in the context of working with immigrant communities. The study, guided by hermeneutic phenomenology and conducted through qualitative interviews, relies on William Kahn's classical theory of employee engagement and investigates the expression of three components—meaningfulness, safety, and availability—in the work of these individuals. The sample is recruited from library staff serving immigrant populations in large metropolitan libraries in Toronto, Ontario, Canada, and New York City, USA. The study concludes that the most important component of engagement in this research population is the meaningfulness of one's work which, in itself, is a composite and complex concept, elucidated in great detail in the study. Meaningfulness is followed by the availability of energies invested in librarians' workplace roles, with safety as the least significant factor. The study observes that librarians' approach to working with immigrants is akin to following a calling, not simply performing work-related duties. It also notes that the phenomenon of vocational awe influences and accounts for librarians' dedicated and committed service to immigrant communities even when the workplace safety net is tentative and uncertain. These findings provide food for thought to public library managers who wish to support and retain their talented, dedicated, and culturally competent staff.